Gender and food systems in six African countries: Aligning research, policies and research funding - Elizabeth, Elizabeth; Du Toit, Andrea; Gandidzanwa, Colleta (New Agenda: SA Journal of Social and Economic Policy, 2024)
Research plays a fundamental role in achieving food systems outcomes but research funders and researchers often set agendas that are not necessarily informed by policy needs. This analysis explores synergies between research publications, funding and policy priorities using a gender and food systems lens. In this article the authors argue that gender research is not being adequately leveraged to investigate food systems challenges that are considered national priorities. They call on research funders, researchers and policy-makers to collaborate to define research agendas that address policy needs.